Biomimetics in Tissue Engineering and Regenerative Medicine - Tung, Bui Thanh; Nhat, Bui Son; Hue, Pham Thi Minh; Hai, Nguyen Thanh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2, 2017)
Biomimetics is a growing scientific field which is being more and more widely applied, from industrial production of normal devices to more modern applications such as robotics, electronic chips, nanotechnology as well as medicine and pharmaceuticals. An approach is to utilize biomimetics in tissue engineering and regenerative medicine to meet clinical as well as research and development demands. With past achievements and considering future prospects, this promises to be the key to solve existing problems in medicines.